Face Mask Wearing and Hand Washing Behavior on the Prevention of COVID-19 Infection: A Meta-Analysis - Andi Siswanto; Bhisma Murti; Hanung Prasetya (Masters Program in Public Health, Sebelas Maret University, 2022)
Background: People infected with the COVID-19 virus can infect others through close droplets, these droplets are water-filled particles with a diameter of >5 m - 10 m. ways to reduce or contract COVID-19 by wearing a mask and washing hands both with soap and hand sanitizer. This study aimed to determine the effect of wearing masks and washing hands on the transmission of COVID-19.Subjects and Method: This research is a meta-analysis study using PRISMA flowchart guidelines. The article search process was carried out between 2020-2021 using databases from PubMed, Science direct, and Google Schoolar. The article search was carried out taking into account the eligibility criteria defined in the PICO model. Population= community. Intervention= use masks and wash hands. Comparison= do not use masks and wash hands. Outcome= infection with COVID-19. The keywords used are